Aplikasi Monitoring Persediaan Barang Berbasis Web Pada Koperasi Pegawai Logistik Dolog Semarang Menggunakan Barcode Reader - Jarot Dian; Fujiama Diapoldo Silalahi (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2021)
Stock reports on purchases and sales of a period. useful for helping employees to assess the amount of inequality in the flow of purchases, monitor stock / inventory of goods, and provide reports both purchase reports, sales reports, stock condition reports, and profit / profit reports to management to determine further business policies The process of recording transactions in a conventional or paper-based manner is identical with several weaknesses, namely easily damaged, difficult / long when looking for stored data, difficult / long when it comes to generating reports. These weaknesses can be corrected by implementing computer-based monitoring applications. If the monitoring application is planned/made properly, the computer-based information system is relatively safer. The model to be developed refers to the Research and Development (R&D) model from Borg and Gall and the tools used and the tools used to design the system are use case diagrams, sequence diagrams, activity diagrams, and class diagrams. while the implementation of making stock/inventory monitoring applications is done with PHP web-based programming and databases using MySQL. This application can help and get more accurate information about the stock data of goods that have run out.